The working results of the research institutions of the Russian federation on sorghum - S. I. Gorpinichenko; N. A. Kovtunova; V. V. Kovtunov (Зерновое хозяйство России, 2018)
S.I. Gorpinichenko, Candidate of Agricultural Sciences; N.A. Kovtunova, Candidate of Agricultural Sciences; V.V. Kovtunov, Candidate of Agricultural Sciences FSBSI “Agricultural Research Center ‘Donskoy” (347740, Zernograd, Nauchny Gorodok, 3; email: vniizk30@mail.ru) The working results of the research institutions of the Russian federation on sorghum The article presents the complete analysis of the data concerning sorghum taken from the State List of the Breeding Achievements for 2016. About 20 research institutions are conducting breeding work in the selection of varieties and hybrids of sorghum in Russia, among them such leading establishments as the FSBSI ARRI of Grain Crops named after I.G. Kalinenko, FSBSI Russian RI o Sorghum and Maize, FSBSI Stavropol RIA, FSBSI Nizhne-Volzhsky RIA, FSBSI RIA of South-East and the Academy of Bio and Nature resources, FSAEI HE Crimea federal University named after V.I. Vernadsky. There are 221 sorghum varieties and hybrids, including 55 varieties and 39 hybrids of grain sorghum, 35 varieties and 10 hybrids of sweet sorghum, 29 sorghum-Sudan hybrids, 39 varieties of Sudan grass, 13 varieties of broomcorn and 2 varieties of perennial sorghum registered in the State List in 2016, among which the share of 6 major research institutions in Russia accounts for 118 (53%) sorghum varieties and hybrids. Analyzing the distribution of sorghum varieties and hybrids according to the date of introduction into the State List, we have found that for the last years Russia has been conducting a successful breeding work with grain sorghum, sweet sorghum and sorghum-Sudan hybrids, among which the new (less than 5 years) varieties account 40-53%. For the last six years (2011-2016) the leading institutions developed and introduced into the State List 22 varieties and hybrids of grain sorghum, 14 varieties of sweet sorghum, 8 varieties of Sudan grass, 8 sorghum-Sudan hybrids and 2 varieties of broomcorn.